Ceftaroline fosamil and treatment of acute bacterial skin and skin structure infections: CAPTURE study experience. (December 2013) - Santos, Paul D.; Davis, Amanda; Jandourek, Alena; Smith, Alexander; David Friedland, H.
Abstract : The Clinical Assessment Program and TEFLARO Utilization Registry (CAPTURE) is a multicentre retrospective cohort study in the USA describing treatment of acute bacterial skin and skin structure infection (ABSSSI) with ceftaroline fosamil (CPT-F). Charts for review were chosen by random selection. Among 647 evaluable patients, 52% were obese, 46% had diabetes mellitus (DM), and 19% had peripheral vascular disease (PVD). Methicillin-resistant Staphylococcus aureus (MRSA) was recovered in 28% and methicillin-susceptible S. aureus (MSSA), 11%. Antibiotics were administered prior to CPT-F treatment in 80%, and concurrently in 39%. Clinical success overall was 85%; in patients with DM, 83%; with PVD, 76%; and in obese patients, 88%. Clinical success was ≧ 79% across all infection types; 81% for MRSA and 83% for MSSA; and 86% for ceftaroline monotherapy and 84% for concurrent therapy. These high clinical success rates support CPT-F as an effective treatment option for ABSSSI, including infections due to MRSA and patients with significant co-morbidities.